Cellulase enzyme production of post-harvest fungi under the influence of carbon and nitrogen sources - Rajmane, S D; Korekar, S L (Current Botany, 2012)
Present research work embodied the effect of nutritional sources like carbon and nitrogen on cellulase enzyme production of post-harvest fungi. It was found that, among carbon sources fructose and sucrose stimulated cellulase activity, while lactose, CMC and starch inhibited the cellulase activity of test fungi. Nitrate source like sodium nitrate, sodium nitrite and calcium nitrate stimulated the cellulase activity while, ammonium sources in the form of nitrate, phosphate and sulphate were proved inhibitory for cellulase production of all post-harvest fungi.